Overexpressing GRE3 in Saccharomyces cerevisiae enables high ethanol production from different lignocellulose hydrolysates - Wang, Haijie; Cao, Limin; Li, Qi; Wijayawardene, Nalin N.; Zhao, Jian; Cheng, Min; Li, Qi-Rui; Li, Xiaobin; Promputtha, Itthayakorn; Kang, Ying-Qian (Frontiers in Microbiology, 2022)
Genetically modified strains for efficient use of xylose and developing lignocellulosic hydrolysates play an essential role in facilitating cellulosic ethanol production. Here we present a promising strain GRE3OE via GRE3 overexpressed in a previously reported Saccharomyces cerevisiae strain WXY70. A comprehensive evaluation of the fermentation level of GRE3OE in alkaline-distilled sweet sorghum bagasse, sorghum straw and xylose mother liquor hydrolysate. Under simulated corn stover hydrolysate, GRE3OE produced 53.39 g/L ethanol within 48 h. GRE3OE produced about 0.498 g/g total sugar in sorghum straw hydrolysate solution. Moreover, GRE3OE consumed more xylose than WXY70 in the high-concentration xylose mother liquor. Taken together, GRE3OE achieved remarkable fermentation efficiencies in three kinds of hydrolysates solution, which outperformed the previous strain WXY70.